RANCANG BANGUN DAN UJI KINERJA PENERAPAN TEKNIK IRIGASI TETES PADA LAHAN KERING - Muanah Muanah; Karyanik Karyanik; Erni Romansyah (Universitas Muhammadiyah Mataram, 2020)
The purpose of this study was to design and test the performance of drip irrigation techniques on dry land. This research method used a completely randomized design with 3 treatments, namely the faucet slope of 150 , 450, and 900 with 4 replications. In order to obtain 12 experimental sample units. Furthermore, the design results were carried out by testing the droplet discharge, uniformity coefficient, wetted soil area, and the amount of water needed during the vegetative growth of tomato plants. The test results based on the discharge value and the uniformity of drops show that the drip irrigation technique design is very good for application on dry land. Based on the discharge value, the wetted area is obtained with a wetting width of 25 cm and a depth of up to 35 cm. So that during the vegetative growth of tomato plants in treatment 150 requires 10200 ml / day of water, 12200 ml / day in treatment 450 , and 30800 ml / day in treatment 900 . Seeing the effect on tomato plant growth, it can be concluded that 150 is the best treatment to apply. on dry land.